2020
DOI: 10.1177/1120672120960333
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for central retinal vein occlusion in young adults

Abstract: Purpose: Several risk factors have been identified for central retinal vein occlusion (CRVO) in older population. CRVO in young is uncommon, and the risk factors for this group are unclear. This large retrospective, cross-sectional study used the National Inpatient Sample (NIS) database to evaluate the risk factors for CRVO in patients 18 to 40 years of age. Methods: The 2002 to 2014 NIS database was used. All patients 18 to 40 years of age with a primary diagnosis of CRVO were identified. Age- and gender-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Instead of glaucoma, there are other diseases which might be risk factors of RVO. Retinal vasculitis may be a more relevant risk factor in young CRVO patients ( 124 ). Central Serous Chorioretinopathy (CSCR) is idiopathic and often recurs.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Instead of glaucoma, there are other diseases which might be risk factors of RVO. Retinal vasculitis may be a more relevant risk factor in young CRVO patients ( 124 ). Central Serous Chorioretinopathy (CSCR) is idiopathic and often recurs.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Thus, CRVO is generally considered a disease of the elderly. In younger patients, hypercoagulable state has been found to be significantly associated with CRVO; however, diabetes mellitus and hypertension were not significant [ 12 ]. Individuals with SARS-CoV-2 infection may have a number of coagulation abnormalities suggesting a hypercoagulable state, which has been called COVID-19 associated coagulopathy [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of 95 patients diagnosed with CRVO between 18 and 40 years of age, Chen et al identified that statistically significant (p<0.001) risk factors for CRVO in young adults included primary open angle glaucoma, retinal vasculitis, pseudotumor cerebri, hypercoagulable state, hyperlipidemia, and a prior history of venous thromboembolic disease. 54 , 55 Other studies have identified that CRVO in young adults may be linked to smoking, migraine headaches, collagen vascular disease, medications (oral contraceptives, diuretics, sympathomimetics), and thrombophilia. 49 , 55 , 56 , 57 , 58 , 59 , 60 Young adults presenting with RVO may need a hypercoagulability workup to exclude systemic coagulopathies requiring anticoagulation, such as protein C and S deficiency, Factor V Leiden mutation, hyperhomocysteinemia, antiphospholipid antibody syndrome, prothrombin gene mutation, antithrombin deficiency, hyperviscosity syndrome, amongst others.…”
Section: Discussionmentioning
confidence: 99%
“… 54 , 55 Other studies have identified that CRVO in young adults may be linked to smoking, migraine headaches, collagen vascular disease, medications (oral contraceptives, diuretics, sympathomimetics), and thrombophilia. 49 , 55 , 56 , 57 , 58 , 59 , 60 Young adults presenting with RVO may need a hypercoagulability workup to exclude systemic coagulopathies requiring anticoagulation, such as protein C and S deficiency, Factor V Leiden mutation, hyperhomocysteinemia, antiphospholipid antibody syndrome, prothrombin gene mutation, antithrombin deficiency, hyperviscosity syndrome, amongst others. 59 , 61 The patients included in the present series were negative for thrombophilia according to extensive laboratory evaluations done by the contributing ophthalmologists and the appropriate medical providers.…”
Section: Discussionmentioning
confidence: 99%